Occurrence and Molecular Characterization of Noroviruses in Korean Surface Water Between 2007 and 2010 - Lee, Gyu-Cheol; Kim, Min-jeong; Kim, Jong Ik; Lee, Chan Hee (Journal of microbiology and biotechnology, 2014)
The occurrence of human norovirus (NoV) genogroup I (GI) and genogroup II (GII) strains was investigated in Korea. Between 2007 and 2010, 265 samples were collected from 89 Korean water source locations. NoV GI was detected in 4.5% and NoV GII in 1.5%. Samples collected in winter had the highest occurrence; 9.4% for NoV GI and 6.3% for NoV GII. NoV GI detection was highest in groundwater, with the next highest in river water and the lowest in lake water (5.9%, 5.4%, and 1.6%, respectively), and NoV GII was found only in river water. When three representative Korean basin systems (Han (H)-, Geum/Seom (G/S)-, and Nakdong (N)-river basins) were compared, both NoV genogroups were high in the G/S-, but absent in the H- river basin. The most prevalent genotypes within the GI and GII groups were GI.5 and GII.4, respectively. The NoVs found in surface water were identical to those found in patients and those found in groundwater. The NoVs appeared to be transmitted from the patient to the surface water, and then to the groundwater, suggesting a fecal-oral route of transmission. This is the first nationwide surveillance of NoV in major Korean water sources.